El régimen desequilibrado del incumplimiento en los contratos del Estado - Huapaya Tapia, Ramón Alberto (2021)
Contracts are celebrated to be complied with. Therefore, breaches of contract are always an irregular and undesirable situation. That being the case, the law guarantees several protection measures against non-compliance, both in private and in public contracts. In the latter case, since the breach can come from either the contractor or the State, the law protects them both. However, Peruvian regulations do not establish the same consequences for the same occurrence, and as a result there are more burdensome consequences if the party which incurred in non-compliance was the contractor. This article seeks to explain that differentiation, through a critical analysis.